Historical and current perspectives on stress and health - Perrewe, Pamela L.; Ganster, Daniel C. (Research in occupational stress and well being ;, 2002)
This is an annual research series devoted to the examination of occupational stress, health and well being, with particular emphasis on the multi-disciplinary nature of occupational stress. The intent is to pull together the various streams of research from a variety of disciplines to better capture the significant bodies of work in occupational stress and well being. It provides a multidisciplinary and international perspective that gives a thorough and critical assessment of issues in occupational stress and well being. The theme for this volume, Historical and Current Perspectives on Stress and Health focuses on two main concerns: historical as well as current perspectives to occupational stress research and an emphasis on the healthy individual and organization.